Effect of water flow on performance of building integrated semi-transparent photovoltaic thermal system: A comparative study. (1st November 2018) - Mishra, G.K.; Tiwari, G.N.; Bhatti, T.S.
Highlights: A validated periodic thermal model for the BiSPVT system with intermittent duration of water flow. Analytical expression of PV cell temperature for RtSPV system and experimental validation. Compared performance of the BiSPVT system with water flow and the RtSPV system without water flow. Abstract: In this paper, a periodic thermal model has been developed for a building integrated semi-transparent photovoltaic (PV) thermal (BiSPVT) system with intermittent water flow (from 0945 h to 1415 h) over the PV array. The model is based upon the energy balance equations formulated at the various nodes of the system. Further, to validate the theoretical model, an experiment has been conducted on a BiSPVT system installed at SODHA BERS Complex, Varanasi, India on 24th September 2017 (clear day). It has been found through the periodic model that with a water flow rate of 1.81 kg/sec over the PV array, there is a decrease in the PV cell temperature by 20.00 °C. The correlation coefficient and root mean square deviation have been used to find the degree of resemblance between the theoretical and the experimental results. Furthermore, a performance comparison of the BiSPVT system (with water flow) and a rooftop semi-transparent photovoltaic (RtSPV) system (without water flow) installed at the same complex has been carried out for the same day. The orientation, the specifications of the PV modules and the additional circuitry involved with both the systems are identical except for minor difference in the tilt angle. The net measured electrical output of the BiSPVT system with water flow was found to be 10.14 kWh which is 1.44 kWh higher than that obtained from the RtSPV system. In addition to the higher electrical energy, the thermal energy generated by BiSPVT system was 379.82 kWh.